2015
DOI: 10.1557/jmr.2015.74
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron radiation investigations of microstructural evolutions of ODS steels and Zr-based alloys irradiated in nuclear reactors

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…In both cases, average nanocluster size decreases while number density increases with dose above 1 dpa. The inverse relationship between size and number density has been observed elsewhere in literature [72,84,88,101], and is akin to inverse Ostwald ripening, which has been previously described in the context of ion beaminduced size refinement of embedded metallic nanoparticles [58,75,77,78,205], an emerging research area in nanoelectronics. Through inverse Ostwald ripening, smaller nanoclusters nucleate and grow at the expense of larger nanoclusters, due to the competing mechanisms of ballistic dissolution and diffusion-driven nanocluster growth, with the net result being a reduced average cluster size and increased number density.…”
Section: Ods Oxidesmentioning
confidence: 66%
See 4 more Smart Citations
“…In both cases, average nanocluster size decreases while number density increases with dose above 1 dpa. The inverse relationship between size and number density has been observed elsewhere in literature [72,84,88,101], and is akin to inverse Ostwald ripening, which has been previously described in the context of ion beaminduced size refinement of embedded metallic nanoparticles [58,75,77,78,205], an emerging research area in nanoelectronics. Through inverse Ostwald ripening, smaller nanoclusters nucleate and grow at the expense of larger nanoclusters, due to the competing mechanisms of ballistic dissolution and diffusion-driven nanocluster growth, with the net result being a reduced average cluster size and increased number density.…”
Section: Ods Oxidesmentioning
confidence: 66%
“…2.13 is proportional to φ), where φ is the irradiation flux [59,69]. Conversely, other irradiation studies have shown evidence of reduction in average nanocluster size [70] and even of haloing [71,72], in which a high density of smaller nanoclusters nucleate around, and at the expense of, larger nanoclusters. This trend is fundamentally the opposite that of Ostwald ripening, and is commonly referred to as inverse Ostwald ripening (Section 2.4.5).…”
Section: Radiation-enhanced Diffusionmentioning
confidence: 99%
See 3 more Smart Citations